Pemodelan dan Simulasi Penghitungan Matematika Menggunakan Aplikasi Matlab - Retnoningsih, Dwi (JURNAL GAUNG INFORMATIKA, 2009)
Calculate simple math might be resolved manually. But complex calculations such as Array, Matrix, and polynomial may require considerable time to complete. So in this study the authors make the modeling and simulation to assist the process for faster computation. The purpose of this research is to make the modeling and simulation of a simple mathematical operation, array of one-dimensional, two-dimensional arrays, matrices, and polynomial. This research resulted in the modeling and simulation of a simple mathematical operation, array of one-dimensional, two-dimensional arrays, matrices, and polynomial using Matlab 6.0 application tool